Nutrition and Exercise in Critical Illness Trial (NEXIS Trial): a protocol of a multicentred, randomised controlled trial of combined cycle ergometry and amino acid supplementation commenced early during critical illness. Issue 7 (31st July 2019) - Heyland, Daren K; Day, Andrew; Clarke, G John; Hough, Catherine (Terri); Files, D Clark; Mourtzakis, Marina; Deutz, Nicolaas; Needham, Dale M; Stapleton, Renee
Abstract : Introduction: Survivors of critical illness often experience significant morbidities, including muscle weakness and impairments in physical functioning. This muscle weakness is associated with longer duration mechanical ventilation, greater hospital costs and increased postdischarge impairments in physical function, quality of life and survival. Compared with standard of care, the benefits of greater protein intake combined with structured exercise started early after the onset of critical illness remain uncertain. However, the combination of protein supplementation and exercise in other populations has demonstrated positive effects on strength and function. In the present study, we will evaluate the effects of a combination of early implementation of intravenous amino acid supplementation and in-bed cycle ergometry exercise versus a 'usual care' control group in patients with acute respiratory failure requiring mechanical ventilation in an intensive care unit (ICU). Methods and analysis: In this multicentre, assessor-blinded, randomised controlled trial, we will randomise 142 patients in a 1:1 ratio to usual care (which commonly consists of minimal exercise and under-achievement of guideline-recommended caloric and protein intake goals) versus a combined intravenous amino acid supplementation and in-bed cycle ergometery exercise intervention. We hypothesise that this novel combined intervention will (1) improve physical functioning at hospital discharge; (2) reduce muscle wasting with improved amino acid metabolism and protein synthesis in-hospital and (3) improve patient-reported outcomes and healthcare resource utilisation at 6 months after enrolment. Key cointerventions will be standardised. In-hospital outcome assessments will be conducted at baseline, ICU discharge and hospital discharge. An intent-to-treat analysis will be used to analyse all data with additional per-protocol analyses. Ethics and dissemination: The trial received ethics approval at each institution and enrolment has begun. These results will inform both clinical practice and future research in the area. We plan to disseminate trial results in peer-reviewed journals, at national and international conferences, and via nutritional and rehabilitation-focused electronic education and knowledge translation platforms. Trial registration number: NCT03021902 ; Pre-results.